Harmonics modeling and harmonic activity analysis of equipments with switch mode power supply using MATLAB and Simulink - Acarkan, B.; Erkan, K. (IEEE, 2007)
Power quality problems are increasing with the widespread use of electronic equipments, which cause harmonic distortion of voltages and currents. Individually, a low power single-phase nonlinear load may not pose many serious harmonic problems but large concentrations of these loads have the potential to raise harmonic voltages and currents to unacceptable levels and harmonic current pollution is a one of the major power quality problem in electrical power systems. In this study, nonlinear resistance and harmonic models of the equipments with switch mode power supply (SMPS) are carried out using MATLAB((R)). Afterwards, Simulink((R)) single-phase and three-phase simulations are developed for both phase and neutral harmonic activity analysis. The symmetrical components theory is implemented under balanced nonsinusoidal conditions.
Keywords: harmonics; power quality; nonlinear modeling; the symmetrical components; MATLABO (R); Simulinko (R); Automation & Control Systems; Engineering; Transportation